Making sense of space: mapping and materializing panoptic features in research with youth and teachers. Issue 1 (2nd January 2022) - Adams, Erin
ABSTRACT: This article describes a study wherein teachers talked about school architecture by using their bodies as well as their voices while analysing maps youth drew of their schools. The youths' maps and the teachers' discussions revealed evidence of their tacit understanding of panoptic surveillance. This may be evocative of the ways panoptic architecture and surveillance work on bodies in ways that are both seen and unseen. The author theorizes the implications of these connections for teacher education, including the ways teachers may be primed to perpetuate the same sorts of surveillances they experienced.